Adherence of probiotic bacteria to human colon epithelial cells and inhibitory effect against enteric pathogens – In vitro study. (21st April 2016) - Adriana, Nowak; Ilona, Motyl; Katarzyna, Śliżewska; Zdzisława, Libudzisz; Elżbieta, Klewicka
Abstract : The aim of this study was to determine the anti‐adherence properties of three probiotic lactobacillus strains ( Lb. rhamnosus 0900, Lb. rhamnosus 0908 and Lb. casei 0919), and their mixture against pathogens: Escherichia coli ATCC 10536, Salmonella enterica serovar Typhimurium ATCC 14028 and Candida albicans ATCC 10231 using Caco‐2 human colon adenocarcinoma cells. All strains of lactobacilli and the probiotic mixture to the greatest extent inhibited adherence of S.  Typhimurium, up to 91%. Lb. rhamnosus 0900 inhibited E. coli by 75.9%, and Lb. casei 0919 decreased adherence of C. albicans by 49%. All pathogens activated the adherence of the mixture of probiotic bacteria.